Let's Sketch in 360º: spherical perspectives for virtual reality panoramas - Araújo, António (2018)
In this workshop we will learn how to draw a 360-degree view of our environment using spherical perspective, and how to visualize these drawings as immersive panoramas by uploading them to virtual reality platforms that provide an interactive visualization of a 3D reconstruction of the original scene. We shall show how to construct these drawing in a simple way, using ruler and compass constructions, facilitated by adequate gridding that takes advantage of the symmetry groups of these spherical perspectives. We will consider two spherical perspectives: equirectangular and azimuthal equidistant, with a focus on the former due to its seamless integration with visualization software readily available on social networks. We will stress the relationship between these panoramas and the notion of spherical anamorphosis.